Aghayeva, Nigar - (:unkn) unknown (My University, 2026)
Nigar Aghayeva is a Lecturer at the Department of Foreign Languages, Azerbaijan University of Architecture and Construction (AzUAC). She graduated with distinction from Azerbaijan University of Languages, earning a Bachelor's degree in English Language and Literature in 2010 and a Master's degree in Foreign Country Literature in 2012. Since 2016, she has been teaching at AzUAC, and in 2025 she completed her PhD research at Azerbaijan University of Languages on Issues of Utopia and Dystopia in Arthur C. Clarke's Science Fiction Works. Her research interests include English language teaching, English for Academic Purposes (EAP), English for Specific Purposes (ESP), science fiction literature, utopian and dystopian studies, and academic writing. She is the author of the Illustrative Technical Dictionary and has published 16 journal articles, 20 conference papers, and three curriculum programmes. She has participated in numerous international professional development programmes, including those offered by the University of Leicester, Sorbonne University, Cambridge English, British TESOL, and the U.S. Department of State's American English Live series. She also completed an academic mobility programme at Kokand University under the Orhun Exchange Programme.